People with intellectual and mental disabilities in the social protection system in Serbia between community and institutionalization - Stankovic, Dragana; Brkic, Miroslav (Ревија за социјална политика/Journal of Social Policy, 2015)
The process of deinstitutionalization is one of the directions of thesocial protection system reform in Serbia that has started at the beginningof the year 2000 and as one of the reform’s priorities is incorporated instrategic documents and laws.In terms of human rights of persons with intellectual and mentaldisabilities, the institutions, but also society as a whole, show to a greatextent insufficient focus and commitment. Compliance with the standardsdefined by the UN Convention on the Rights of Persons with Disabilities,ratified by Serbia what makes it legally binding document, has remainedjust at the level of the governmental formal commitment.Despite legislative changes aimed at protecting the rights of peoplewith intellectual and mental disabilities, the number of those people in theresidential institutions is still high. The key assumption of thedeinstitutionalization process - development of community-based services,what should ensure getting the necessary support in the natural environment (and prevention of the institutional care as the same time),hasn’t kept the anticipated pace.
Keywords: people with intellectual and mental disabilities; institutionalization; the social protection system; community-basedservices; deinstitutionalization